2021
DOI: 10.1136/bmjopen-2020-044160
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surgical capacity in Chiapas, Mexico: a cross-sectional study of the public and private sector

Abstract: IntroductionSurgical, anaesthesia and obstetric (SAO) care are essential, life-saving components of universal healthcare. In Chiapas, Mexico’s southernmost state, the capacity of SAO care is unknown. This study aims to assess the surgical capacity in Chiapas, Mexico, as it relates to access, infrastructure, service delivery, surgical volume, quality, workforce and financial risk protection.MethodsA cross-sectional study of Ministry of Health public hospitals and private hospitals in Chiapas was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, seeking care from the private sector has its own accompanying fees, making expendable resources key to accessing care. A 2020 study found surgery in the private sector significantly more likely to cause catastrophic expenditure [ 14 ]. These costs put patients at risk of joining the over 81 million people who experience catastrophic expenditure from surgical costs annually, often leading to generational poverty through the selling of essential property [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seeking care from the private sector has its own accompanying fees, making expendable resources key to accessing care. A 2020 study found surgery in the private sector significantly more likely to cause catastrophic expenditure [ 14 ]. These costs put patients at risk of joining the over 81 million people who experience catastrophic expenditure from surgical costs annually, often leading to generational poverty through the selling of essential property [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite universal health coverage, large disparities exist in healthcare access and quality in the southern state of Chiapas, where roughly 30% of the population lives in extreme poverty [ 12 , 13 ]. In recent studies, the public surgical system in Chiapas was found to have significant capacity limitations in areas such as infrastructure, diagnostic capabilities, and workforce [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous literature, we categorised equipment and consumables into anaesthetic equipment, surgical equipment, and consumables (S2). 34 , 35 Descriptive comparisons were made without statistical inference.…”
Section: Methodsmentioning
confidence: 99%